Intravenous Lidocaine Efficacy in Preventing Succinylcholine-Induced Postoperative Myalgia in Surgical Adult Patients at Tikur Anbessa Specialized Hospital - Aligaz, Esubalew Muluneh; Senait Aweke Yadeta; Amanuel Sisay Endeshaw; Mulualem Sitot Fekede; Hirbo Samuel Hirbo (HM Publisher, 2024)
Introduction: Medical professionals exclusively utilize succinylcholine as a depolarizing muscle relaxant. Some of the negative symptoms include fasciculation, myalgia, muscle spasms, and hyperkalemia. The study aimed to evaluate the efficacy of intravenous lidocaine in preventing succinylcholine-induced postoperative myalgia. Methods: A prospective cohort study was undertaken on 80 elective surgery patients. Participants were categorized into two groups: one group received intravenous lidocaine (the exposed group), and the other did not receive lidocaine (the control group). The study participant was chosen using a rigorous random sampling procedure. Data collectors monitored patients for post-operative myalgia at 12, 24, and 48 hours following the procedure. We analyzed the data using SPSS version 26. A P-value below 0.05 indicated statistical significance. Results: Demographic and clinical data in both groups are similar, with a p-value greater than 0.05. The total incidence rate of succinylcholine-induced postoperative myalgia was 39.3%. 22.5% of the group that received lidocaine experienced postoperative myalgia, compared to 60% of the group that did not receive lidocaine. The group that received lidocaine had lower postoperative myalgia severity generated by succinylcholine compared to the group that did not receive lidocaine, with percentages of 42.9% against 53.3% for mild myalgia, and 15.8% versus 84.3% for moderate myalgia, respectively, with a p-value of 0.001. Conclusion: Administering lidocaine intravenously prior to surgery effectively reduced the occurrence and intensity of succinylcholine-induced muscle pain after the operation.